2024
DOI: 10.1101/2024.03.12.584673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multi-modal image fusion workflow incorporating MALDI imaging mass spectrometry and microscopy for the study of small pharmaceutical compounds

Zhongling Liang,
Yingchan Guo,
Abhisheak Sharma
et al.

Abstract: Multi-modal imaging analyses of dosed tissue samples can provide more comprehensive insight into the effects of a therapeutically active compound on a target tissue compared to single-modal imaging. For example, simultaneous spatial mapping of pharmaceutical compounds and endogenous macromolecule receptors is difficult to achieve in a single imaging experiment. Herein, we present a multi-modal workflow combining imaging mass spectrometry with immunohistochemistry (IHC) fluorescence imaging and brightfield micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…For example, pan sharpening applications of image fusion fuse high spatial resolution panchromatic images with low spatial resolution multispectral images to generate a high spatial resolution multispectral image. , Van de Plas et al demonstrated image fusion using mass spectrometry images by combining molecular information from the mass spectrometer with fine-grained texture information from optical microscopy images to generate a mass spectrometry image predicted to higher spatial resolution (i.e., compared to the microscopy image) . Our group has utilized this image fusion workflow to enhance imaging mass spectrometry spatial resolution for better integration with high spatial resolution imaging modalities (e.g., fluorescence and brightfield microscopy) in neuropharmacology studies . Image fusion has also been used to combine multiple mass spectrometry-based images.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, pan sharpening applications of image fusion fuse high spatial resolution panchromatic images with low spatial resolution multispectral images to generate a high spatial resolution multispectral image. , Van de Plas et al demonstrated image fusion using mass spectrometry images by combining molecular information from the mass spectrometer with fine-grained texture information from optical microscopy images to generate a mass spectrometry image predicted to higher spatial resolution (i.e., compared to the microscopy image) . Our group has utilized this image fusion workflow to enhance imaging mass spectrometry spatial resolution for better integration with high spatial resolution imaging modalities (e.g., fluorescence and brightfield microscopy) in neuropharmacology studies . Image fusion has also been used to combine multiple mass spectrometry-based images.…”
Section: Introductionsupporting
confidence: 91%
“…The accuracy of each model was evaluated based on previously described parameters. , This includes visual inspection of the spatial sharpening of the predicted ion images, calculation of the correlation scores (i.e., the R 2 value obtained by plotting the intensity values from the ion image before image fusion against those of the predicted image using the plotregression function in MATLAB), and calculation of the average absolute residual (eq ): n = 1 n = N abs false( I ( original ) n I ( predicted ) n false) N where N is the number of total pixels, I (original) n is the intensity value of the n th pixel for the ion image before image fusion, and I (predicted) n is the intensity value of the n th pixel for the predicted ion image. A smaller average absolute residual indicates the model more accurately predicts the intensity values of the ion image.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation